Implementasi Pendaftaran UMKM Desa Pematang Kasih Kecamatan Pantai Cermin ke Google Maps sebagai Strategi Promosi Lokal - Khairani Simatupang; Feri Arifin; Khairunnisa Khairunnisa (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The Community Service Program (KKN) implemented in Pematang Kasih Village, Pantai Cermin District, focused on empowering Micro, Small, and Medium Enterprises (MSMEs) through the implementation of business unit registration on Google Maps as a local promotion strategy. The main problems faced by MSMEs in this village are limited access to digital promotion, low technological mastery, and lack of business visibility in the online realm. The method used was participatory action based on technical assistance, where students acted as facilitators and direct assistants at every stage of the activity. The implementation process began with the socialization stage of the importance of business digitalization, identification of MSME potential, technical training on creating a Google My Business account, and direct practice of registering a business on Google Maps. All stages were carried out collaboratively by involving MSME owners so that they could independently manage their business profiles after the mentoring ended. The program results showed a significant increase in the number of MSMEs registered on Google Maps, an increase in business actors' understanding of digital promotion strategies, and the emergence of a collective awareness of the importance of technology adaptation in village economic development. Thus, registering MSMEs on Google Maps can be an effective, inexpensive, and sustainable local promotion strategy in expanding marketing reach while increasing the competitiveness of village MSMEs.